AUSTRALIAN NATIONAL IDENTITY, NATURE, AND HUMAN RELATIONSHIPS IN MURRAY BAIL’S WORKS - Muxammedova Nafisa Kamolovna, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article investigates the interrelationship between Australian national identity, representations of nature, and human relationships in Murray Bail’s fiction. Drawing on scholarly analyses by Herbillon, Ackland, and ecocritical studies of Eucalyptus, as well as theoretical insights from postcolonial and environmental research, the study argues that Bail destabilizes fixed national identity by situating it within dynamic interactions between self, landscape, and community. Using a qualitative textual analysis informed by postcolonial theory and ecocriticism, the findings demonstrate that nature in Bail’s works operates as an active agent, shaping both narrative structure and human relationships. Ultimately, Bail’s fiction proposes a relational model of identity grounded in environmental and social interconnectedness.